Evidence That Phosphorylation of the α-Subunit of eIF2 Does Not Essentially Inhibit mRNA Translation in Wheat Germ Cell-Free System - Zhigailov, Andrey V.; Alexandrova, Alena M.; Nizkorodova, Anna S.; Stanbekova, Gulshan E.; Kryldakov, Ruslan V.; Karpova, Oxana V.; Polimbetova, Nailya S.; Halford, Nigel G.; Iskakov, Bulat K. (Frontiers in Plant Science, 2020)
A mechanism based on reversible phosphorylation of the alpha-subunit of eukaryotic initiation factor 2 (eIF2alpha) has been confirmed as an important regulatory pathway for inhibition of protein synthesis in mammalian and yeast cells, while plants constitute the significant exception. We studied the induction of TaeIF2alpha phosphorylation in germinated wheat (Triticum aestivum) embryos subjected to different adverse conditions. Data confirmed that formation of TaeIF2(alphaP) was not a general response, as no phosphorylation was observed under salt, oxidative or heat stress. Nevertheless, treatment by salicylic acid, UV-light, cold shock and histidinol did induce phosphorylation of TaeIF2alpha of wheat, as has been established previously for AteIF2alpha in Arabidopsis (Arabidopsis thaliana). Influence of TaeIF2alpha phosphorylation on translation of reporter mRNA with different 5′-untranslated regions (5′UTRs) was studied in wheat germ cell-free system (WG-CFS), in which TaeIF2alpha was first phosphorylated either by heterologous recombinant human protein kinase, HsPKR (activated by double-stranded (ds)RNA), or by endogenous protein kinase TaGCN2 (activated by histidinol). Pre-treatment of WG-CFS with HsPKR in the presence of dsRNA or with histidinol resulted in intense phosphorylation of TaeIF2alpha; however, the translation levels of all tested mRNAs decreased by only 10–15% and remained relatively high. In addition, factor OceIF2 from rabbit (Oryctolagus cuniculus) bound GDP much more strongly than the homologous factor TaeIF2 from wheat germ. Furthermore, factor OceIF2B was able to stimulate guanine nucleotides exchange (GDP to GTP) on OceIF2 but had no effect on the similar exchange on TaeIF2. These results suggest that the mechanism of stress response via eIF2alpha phosphorylation is not identical in all eukaryotes and further research is required to find and study in detail new plant-specific mechanisms that may inhibit overall protein synthesis in plants under stress.